Exposure to endosulfan influences sperm competition in Drosophila melanogaster - Misra, Snigdha (Sci Rep, 2014)
Dwindling male fertility due to xenobiotics is of global concern. Accordingly, male reproductive toxicity assessment of xenobiotics through semen quality analysis in exposed males, and examining progeny production of their mates is critical. These assays, in part, are biased towards monogamy. Females soliciting multiple male partners (polyandry) is the norm in many species. Polyandry incites sperm competition and allows females to bias sperm use. However, consequences of xenobiotic exposure to the sperm in the light of sperm competition remain to be understood. Therefore, we exposed Drosophila melanogaster males to endosulfan, and evaluated their progeny production as well as the ability of their sperm to counter rival control sperm in the storage organs of females sequentially mated to control/exposed males. Endosulfan (2 μg/ml) had no significant effect on progeny production and on the expression of certain genes associated with reproduction. However, exposed males performed worse in sperm competition, both as 1(st) and 2(nd) male competitors. These findings indicate that simple non-competitive measures of reproductive ability may fail to demonstrate the harmful effects of low-level exposure to xenobiotics on reproduction and advocate consideration of sperm competition, as a parameter, in the reproductive toxicity assessment of xenobiotics to mimic situations prevailing in the nature.